ATR-FTIR, FT-NIR and near-FT-Raman spectroscopic studies of molecular composition in human skin in vivo and pig ear skin in vitro. Issue 6 (2008) - Greve Greve, Tanja M. Tanja M.; Andersen Andersen, Kristine B. Kristine B.; Nielsen Nielsen, Ole F. Ole F.
Abstract : ATR-FTIR, FT-NIR and near-FT-Raman spectroscopy were used to characterize the molecular composition of human skin in vivo and pig ear skin in vitro . Due to different measurement depths the spectroscopic techniques reveal the characteristics of different layers of the skin. Tape stripping was used with the ATR-FTIR technique. Spectral differences concerning lipid content and conformation, protein secondary structure or content of water were found with respect to both gender and species (i.e. human versus pig ear) at all measured skin depths. New assignments of so far unassigned lipid and protein peaks in the FT-NIR and ATR-FTIR spectra of skin were made. PCA and PLS models were used to investigate the division of the recorded spectra into groups. With respect to classification of male and female subjects, the PLS discriminant analysis provided a classification accuracy of 64–93% based on the ATR-FTIR spectra and 83–89% based on the Raman spectra. With respect to classification of human skin in vivo and pig ear skin in vitro, the PLS discriminant analysis provided a classification accuracy of 75–100% based on the Raman spectra and 100% based on the ATR-FTIR spectra.